Taxonomic revision of the genus Nychiodes Lederer, 1853 (Geometridae: Ennominae: Boarmiini) with description of three new species—an integrative approach - Wanke, Dominic; Hausmann, Axel; Krogmann, Lars; Petrányi, Gergely; Rajaei, Hossein (Zootaxa, 2020)
The non-European taxa of the genus Nychiodes Lederer, 1853 are revised. Type specimens of all described species and a large series of about 800 additional specimens were morphologically examined. More than 400 genitalia preparations were made and analyzed along with distributional and DNA barcode data. As a result of our integrative taxonomic approach, Nychiodes waltheri saerdabica Wehrli, 1938 syn. nov., is synonymized with N. waltheri Wagner, 1919; N. palaestinensis libanotica Zerny, 1933 syn. nov. is synonymized with N. palaestinensis Wagner, 1919 and the synonymy of N. persuavis Wehrli, 1929 syn. rev. with N. palaestinensis is confirmed; N. admirabila safidaria Wiltshire, 1943 syn. nov. is synonymized with N. admirabila Brandt, 1938; N. agatcha Brandt, 1938 syn. nov., N. subvirida disjuncta Wehrli, 1941 syn. nov. and N. subvirida taftana Brandt, 1941 syn. nov. are synonymized with N. subvirida Brandt, 1938. Also, N. variabila variabila Brandt, 1938 syn. nov., N. variabila opulenta Brandt, 1941 syn. nov., N. divergaria elbursica Wehrli, 1937 syn. nov., N. divergaria fallax Wehrli, 1939 syn. nov. and N. divergaria achtyca Wehrli, 1939 syn. nov. are synonymized with N. divergaria Staudinger, 1892. Nychiodes convergata sp. nov. from Israel, N. mirzayansi sp. nov. from the Iran and N. eberti sp. nov. from Turkey are described. Lecto- and paralectotypes are designated for N. palaestinensis, N. antiquaria, N. divergaria. Furthermore, N. antiquaria is reported as a new species for Pakistan, N. rayatica is reported as a new species for Iran and the hypothetical occurrence of N. amygdalaria in Iran is confirmed. Additionally, N. tyttha needs to be excluded from the genus. Wing pattern, male and female genitalia and diagnostic characters of all examined species are illustrated and distribution maps are provided. Illustrated keys based on genitalia, as well as a complete checklist of the genus is given here.